Communication: Cross-cultural applications of the physician's art - Masi, Ralph (1992)
Cross-cultural care should not be viewed as a problem to be dealt with within a physician's practice. Rather it must be seen as providing a solution to health care within the context of global demographic changes. It is clear that in Canada, as elsewhere, family physicians need to develop a better understanding of the cross-cultural process in order to be able to provide appropriate care for patients who are from culturally diverse backgrounds.